NEK7 Regulates NLRP3 Inflammasome Activation and Neuroinflammation Post-traumatic Brain Injury - Chen, Yuhua; Meng, Jiao; Bi, Fangfang; Li, Hua; Chang, Cuicui; Ji, Chen; Liu, Wei (Frontiers in Molecular Neuroscience, 2019)
As one of the most common causes of mortality and disability, traumatic brain injury (TBI) causes huge psychological and economic burden to patients, families, and societies worldwide. Neuroinflammation reduction may be a favorable option to alleviate secondary brain injuries and ameliorate the outcome of TBI. The nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain-containing 3 (NLRP3) inflammasome has been shown to be involved in TBI. NIMA-related kinase 7 (NEK7) has been identified as an essential mediator of NLRP3 inflammasome activation that is recruited upstream of the formation of inflammasomes in response to NLRP3 activators. However, the underlying mechanism by which NEK7 operates post-TBI remains undefined. In this study, we performed both in vivo and in vitro experiments. Using an in vivo mouse TBI model, mice were administered an intracerebroventricular injection of NEK7-shRNA virus. For the in vitro analysis, primary cortical neurons with NEK7-shRNA were stimulated with LPS/ATP or potassium (K+). We evaluated the effects of NEK7 knock-down on neurological deficits, NLRP3 inflammasomes, caspase-1 activation, and neuronal injury. During the 0–168 h post-TBI period in vivo, NEK7 and NLRP3 inflammasome activation increased in what appeared to be a time-dependent manner. As well as pyroptosis-related markers, caspase-1 activation (p20) and IL-1β activation (p17) were up-regulated. NEK7 down-regulation attenuated neurological deficits, NLRP3 inflammasomes, caspase-1 activation, and neuronal injury. The same phenomena were observed during the in vitro experiments. Furthermore, NEK7 knock-down abolished NLRP3 inflammasome activation and pyroptosis, which were triggered by K+ efflux, and the LPS + ATP-triggered NEK7-NLRP3 complex was reversed in primary cortical neurons placed in 50 mM K+ medium. Collectively, the data demonstrated that NEK7, is a modulator, regulates NLRP3 inflammasomes and downstream neuroinflammation in response to K+ efflux, through NEK7-NLRP3 assembly, pro-caspase-1 recruitment, caspase-1 activation, and pyroptosis in nerve injuries, post-TBI. NEK7 may be a potential therapeutic target for attenuating neuroinflammation and nerve injury post-TBI.